KONTROVERSI POLITIK HUKUM DALAM KEBIJAKAN PEMBATASAN IMPOR KOMODITAS STRATEGIS PERSPEKTIF KEDAULATAN EKONOMI - Rahmat Giling; Mustofa Kamil; Dany Wahyu; Nursalim; Mahmuddin (CV. Lafadz Jaya, 2026)
Policies restricting imports of strategic commodities are an important instrument in achieving a nation’s economic sovereignty. In Indonesia, these policies face a range of complex political and legal controversies, particularly in the context of global economic integration and international trade obligations. This paper analyses the political and legal controversies surrounding policies restricting imports of strategic commodities from the perspective of economic sovereignty, using a normative legal research method supplemented by historical, conceptual and comparative legal approaches. The research findings indicate that there is a tension between the interests of protecting national economic sovereignty and the obligations of international trade liberalisation as stipulated in the General Agreement on Tariffs and Trade/World Trade Organisation. This legal-political controversy is reflected in the dynamics of legislative drafting, which is often ambivalent, inconsistent policy implementation, and selective law enforcement. This paper recommends the need for a reconstruction of legal policy that integrates the principle of economic sovereignty into the framework of international trade law through the utilisation of safeguard mechanisms, general exceptions, and industrial policies consistent with international trade commitments.